Commensal microbiota is hepatoprotective and prevents liver fibrosis in mice. Issue 3 (2nd December 2014) - Mazagova, Magdalena; Wang, Lirui; Anfora, Andrew T.; Wissmueller, Max; Lesley, Scott A.; Miyamoto, Yukiko; Eckmann, Lars; Dhungana, Suraj; Pathmasiri, Wimal; Sumner, Susan; Westwater, Caroline; Brenner, David A.; et al.
Abstract : Translocation of bacteria and their products across the intestinal barrier is common in patients with liver disease, and there is evidence that experimental liver fibrosis depends on bacterial translocation. The purpose of our study was to investigate liver fibrosis in conventional and germ‐free (GF) C57BL/6 mice. Chronic liver injury was induced by administration of thioacetamide (TAA) in the drinking water for 21 wk or by repeated intraperitoneal injections of carbon tetrachloride (CCl4 ). Increased liver fibrosis was observed in GF mice compared with conventional mice. Hepatocytes showed more toxin‐induced oxidative stress and cell death. This was accompanied by increased activation of hepatic stellate cells, but hepatic mediators of inflammation were not significantly different. Similarly, a genetic model using Myd88/Trif‐deficient mice, which lack downstream innate immunity signaling, had more severe fibrosis than wild‐type mice. Isolated Myd88/Trif‐deficient hepatocytes were more susceptible to toxin‐induced cell death in culture. In conclusion, the commensal microbiota prevents fibrosis upon chronic liver injury in mice. This is the first study describing a beneficial role of the commensal microbiota in maintaining liver homeostasis and preventing liver fibrosis.—Mazagova, M., Wang, L., Anfora, A. T., Wissmueller, M., Lesley, S. A., Miyamoto, Y., Eckmann, L., Dhungana, S., Pathmasiri, W., Sumner, S., Westwater, C., Brenner, D. A., Schnabl, B., Commensal microbiota is hepatoprotective and prevents liver fibrosis in mice. FASEB J. 29, 1043–1055 (2015). www.fasebj.org